MiR-185 inhibits 3T3-L1 cell differentiation by targeting SREBP-1*. Issue 9 (2nd September 2017) - Ning, Chunyou; Li, Guilin; You, Lu; Ma, Yao; Jin, Long; Ma, Jideng; Li, Xuewei; Li, Mingzhou; Liu, Haifeng
Abstract : Adipogenesis involves a highly orchestrated series of complex events in which microRNAs (miRNAs) may play an essential role. In this study, we found that the miR-185 expression increased gradually during 3T3-L1 cells differentiation. To explore the role of miR-185 in adipogenesis, miRNA agomirs and antagomirs were used to perform miR-185 overexpression and knockdown, respectively. Overexpression of miR-185 dramatically reduced the mRNA expression of the adipogenic markers, PPARγ, FABP4, FAS, and LPL, and the protein level of PPAR γ and FAS. MiR-185 overexpression also led to a notable reduction in lipid accumulation. In contrast, miR-185 inhibition promoted differentiation of 3T3-L1 cells. By target gene prediction and luciferase reporter assay, we demonstrated that sterol regulatory element binding protein 1 ( SREBP -1) may be the target of miR-185. These results indicate that miR-185 negatively regulates the differentiation of 3T3-L1 cells by targeting SREBP-1, further highlighting the importance of miRNAs in adipogenesis. Abstract : MiR-185 may down-regulate marker genes related to adipocyte differentiation and inhibit 3T3-L1 adipogenesis by targeting SREBP -1.